Answer:
Step-by-step explanation:
[tex]\bold{slope\, (m)=\dfrac{change\ in\ Y}{change\ in\ X}=\dfrac{y_2-y_1}{x_2-x_1}}[/tex]
(−4, 2) ⇒ x₁ = −4, y₁ = 2
(6,−3) ⇒ x₂ = 6, y₂ = −3
So the slope:
[tex]\bold{m=\dfrac{-3-2}{6+4}=\dfrac{-5}{10}=-0.5}[/tex]
The point-slope form of the equation of the line passing through point (x₀,y₀) and with slope m is: y - y₀ = m(x - x₀)
m = -0.5
(−4, 2) ⇒ x₀ = −4, y₀ = 2
Therefore:
y - 2 = -0.5(x - (-4))
y - 2 = -0.5x - 2 {add 2 to both sides}
y = -0.5x ← the slope-intercept form of the equation (b=0)